2020
DOI: 10.3390/agronomy10101453
|View full text |Cite
|
Sign up to set email alerts
|

Fertigation of Maize with Digestate Using Drip Irrigation and Pivot Systems

Abstract: Digestate is a nutrient-rich fertilizer and appropriate techniques are required for its application during the maize season to reduce losses and increase the nitrogen use efficiency (NUE). The performance of two different fertigation techniques (drip irrigation and pivot) were assessed using the digestate liquid fraction. A two-year field test was carried out at two different sites in Lombardy, northern Italy. At each site, fertigation with pivot (P-F, site 1) or drip (D-F, site 2) systems was compared to refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…In our study, the S-index, Topdressing N, and yield in 2017 and 2018 showed different average values between the two years. This was observed throughout the region [50] because of severe biotic stress due to European corn borer (Ostrinia nubilalis) and fungal diseases causing a declining rate of crop production. In general, FR often results in a maize grain yield increase in response to increasing N rates if no water stress occurs [26].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the S-index, Topdressing N, and yield in 2017 and 2018 showed different average values between the two years. This was observed throughout the region [50] because of severe biotic stress due to European corn borer (Ostrinia nubilalis) and fungal diseases causing a declining rate of crop production. In general, FR often results in a maize grain yield increase in response to increasing N rates if no water stress occurs [26].…”
Section: Discussionmentioning
confidence: 99%
“…The available techniques to reduce agricultural NH3 emissions include inter alia covering manure and slurry storage facilities, cooling storage facilities and/or contents, acidifying slurry, stripping NH3, fractioning fertilization during crop growth, and fertigation using slurry or digestate (Rotz et al, 2014;European Commission, 2017). Fertigation is a valid alternative to other fertilization practices, because it can minimize nitrogen loss, while facilitating the utilization of animal (and crop) wastes, thereby contributing to circularity within a farming system (European Commission, 2017;Finzi et al, 2019;Guido et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…The separated digestate is an excellent fertilizer, because the retained nitrogen is in ammoniacal form, which is readily used by plants (Guilayn et al, 2019). However, for the same reason, the potential for NH3 emissions to occur from digestate is high (Guido et al, 2020a). To minimize these emissions, care and attention must be exerted when utilizing this product.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations